Economic stagnation on the territory of Bosnia and Herzegovina during the invasion of Barbarian tribes - Omerčević, Bego (Historical Thought, 2025)
During the 4th and the beginning of the 5th century, there was an intense weakening of the economy on the territory of Bosnia and Herzegovina. This situation was especially influenced by the frequent invasions of barbarian tribes, which were not satisfied only by killing the population and plundering their property, but they also destroyed the material goods, without thinking that the time would come when they would have to rebuild them themselves and create preconditions for the development of economy in order to secure the necessary living conditions. Considering the origins of the barbarians and the areas from which they came to the Roman Empire, with the blooming civilization, their relationship to the population and the material goods found there is quite understandable. Changes of their awareness, as well as certain positive economic trends, occurred at the time of their permanent settlement in this territory (late 5th and the first half of the 6th century). However, such a situation would last only for a short time. During the second half of 6th and at the beginning of the 7th century, barbaric peoples continued with their destructive activities, which eventually led to the total stagnation of the economy on the territory of Bosnia and Herzegovina.